2004
DOI: 10.1007/s11745-004-1225-3
|View full text |Cite
|
Sign up to set email alerts
|

8302A/C and (TTA)n polymorphisms in the HMG‐CoA reductase gene may be associated with some plasma lipid metabolic phenotypes in patients with coronary heart disease

Abstract: HMG-CoA reductase (HMGCR) is a rate-limiting enzyme that participates in cholesterol metabolism. Here we analyzed the 8302A/C and the (TTA)n polymorphisms in the HMGCR gene in 169 Chinese patients with coronary heart disease (CHD) and 161 age-matched controls. Results indicated that the levels of plasma VLDL and TG in patients with the AA genotype of the 8302A/C locus were significantly higher than in patients with other genotypes (P < 0.05). In addition, the frequency of allele A4 of the (TTA)n locus was high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
1
9
1
Order By: Relevance
“…In HA, this is the first association data that showed significant associations between HMGCR haplotypes with multiple lipid/lipoprotein traits, especially with TG, s-LDL, and HDL-c. In CHA, we did not observe any association, although an association between 8302A/C variation of the HMGCR gene and lipids was reported in one Chinese study [33]. It should be noticed that the absence of H2 in CHA and the lack of the distinct, separable H4 and H8 haplotypes in AA and EA could well have accounted for the ethnic differences in the associations.…”
Section: Discussioncontrasting
confidence: 74%
“…In HA, this is the first association data that showed significant associations between HMGCR haplotypes with multiple lipid/lipoprotein traits, especially with TG, s-LDL, and HDL-c. In CHA, we did not observe any association, although an association between 8302A/C variation of the HMGCR gene and lipids was reported in one Chinese study [33]. It should be noticed that the absence of H2 in CHA and the lack of the distinct, separable H4 and H8 haplotypes in AA and EA could well have accounted for the ethnic differences in the associations.…”
Section: Discussioncontrasting
confidence: 74%
“…C) was segregating in commercial pig breeds (Table 3) and showed significant whole-population associations, although at nominal level, with gluteus medius IMF content and serum TG at 45 days of age (Table 4). Similar effects have been described in humans, where analyses of an 830A/C polymorphism in human HMGCR gene resulted in higher levels of circulating low-density lipoprotein and TG in patients with the AA genotype (Tong et al, 2004). Considering the correction for multiple testing, the association tests with LDL-bound cholesterol reached the significance at experiment-wide level (P , 0.006) in family 3 (45 days) and family 5 (190 days), and also with TC in family 3 (45 days).…”
Section: Discussionsupporting
confidence: 69%
“…Expression of this gene represses the expression of low-density lipoprotein (LDL) receptors in liver, altering the serum cholesterol levels (reviewed in Kajinami et al, 2004). In agreement with this, polymorphisms on the human HMGCR gene have been associated with changes in the plasma cholesterol and triglyceride (TG) levels (Tong et al, 2004). Also, mutations resulting in alternative splicing of human exon 13 are a source of serum LDL-cholesterol variation (Burkhardt et al, 2008).…”
Section: Introductionmentioning
confidence: 91%
“…HMG-CoA reductase (HMGCR), a rate-limiting enzyme in cholesterol biosynthesis, is located under our linkage peak (Table 6). Polymorphisms in HMGCR may be associated with plasma lipid levels (75). Further studies will be needed to determine whether the QTL for TC that we found on 8p23 in the total family sample is distinct from our QTL for TG located ‫03ف‬ cM away.…”
Section: Discussionmentioning
confidence: 63%